C-reactive protein estimation: A quantitative analysis for three nonsteroidal anti-inflammatory drugs: A randomized control trial - Gaurav Salgia; Deepak G Kulkarni; Lakshmi Shetty (Wolters Kluwer Medknow Publications, 2015)
Context: C-reactive protein (CRP) estimation for quantitative analysis to assess anti-inflammatory action of nonsteroidal anti-inflammatory drugs (NSAIDs) after surgery in maxillofacial surgery. Aims: This study was to evaluate the efficacy of CRP as a quantitative analysis for objective assessment of efficacy of three NSAIDs in postoperative inflammation and pain control. Settings and Design: The parallel study group design of randomization was done. Totally 60 patients were divided into three groups. CRP was evaluated at baseline and postoperatively (immediate and 72 h) after surgical removal of impacted lower third molar. The respective group received the drugs by random coding postoperatively. Subjects and Methods: The assessment of pain control and inflammation using NSAIDs postoperatively after surgical removal of impacted lower third molar was qualitatively and quantitatively assessed with CRP levels. The blood sample of the patient was assessed immediate postoperatively and after 72 h. The visual analog scale (VAS) was used for assessment of pain and its correlation with CRP levels. Statistical Analysis: Comparison of difference in levels of CRP levels had P < 0.05 with immediate postoperative and baseline levels. The duration of surgery with association of CRP levels P = 0.425 which was nonsignificant. The pain score was increased with mefenamic acid (P = 0.003), which was significant on VAS. Results: Diclofenac had the best anti-inflammatory action. There was a significant increase in CRP levels in immediate postoperative values and 72 h. CRP test proved to be a useful indicator as a quantitative assessment tool for monitoring postsurgical inflammation and therapeutic effects of various anti-inflammatory drugs. Conclusions: CRP test is a useful indicator for quantitative assessment for comparative evaluation of NSAIDs.